Creation of the Venice Commission as Consultative Body of the Council of Europe - M. A. Limonnikova (Московский журнал международного права)
This article deals with a consultative body of the Council of Europe - the European commission for democracy through law (commonly known as the Venice Commission).The author reveals historical and legal reasons of creation of the Venice commission the most important of which are some limitations of State sovereignty on behalf of international organizations. The article also tackles some general aspects of development and using of non binding norms by international organizations and, in particular, by the Council of Europe, for instance, legal opinions of the Venice Commission which, according to the author, are more efficient than obligatory (binding) norms.The mission of the Venice Commission which is to strengthen the Council of Europe principles, such as democracy, human rights and rule of law is also revised.Finally, the author analyzes a legal form of the Venice commission – a partial agreement (only interested member states participate in an activity). The author draws attention to the fact that the Venice commission has now been transformed to an enlarged agreement (all member states participate in its activity as well as some of non-member states) which proves its efficiency and usefulness even if it has only consultative competences.